EFEKTIVITAS PENGGUNAAN GOOGLE CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR ALAT UKUR - Adi Noviantoro; Suparmin; Nurcholish Arifin Handoyono (JURNAL VOKASI DEWANTARA (JVD), 2023)
research intends to decide the viability of the utilization of Google classroom compared to the use of Whatsapp groups on the learning outcomes of class X understudies at SMK Muhammadiyah 1 Sleman for the 2020/2021 scholarly year. This kind of examination is a quasi-experimental design type of nonquivalent control group. Study population is TBSM class X students which consisted of 42 students. Samples were taken randomly, namely class X TBSM A as the exploratory class, while class X TBSM B as the control class, each class comprised of 21 understudies. Information assortment strategies utilizing tests. The data variety instrument used was a different choice test. The information examination strategy utilized graphic, the investigation lprerequisite test utilized the ordinariness test and homogeneity test, while the hypothesis test used the t-test. Research has proven that the learning outcomes of measuring instruments for students who use google classroom are better than being given a whatsapp group to class X understudies at SMK Muhammadiyah 1 Sleman for the 2020/2021 school year.